PENDAMPINGAN OPTIMALISASI PEMBELAJARAN ILMU AGAMA DI TAMAN PENDIDIKAN AL-QUR’AN DARUL MUTTAQIEN DESA NGADIROJO, KECAMATAN SOOKO, KABUPATEN PONOROGO - Harris, Jaudat Iqbal; Umam, Khoirul; Husni, Indra Sholeh; Oktavianos, Vandeber; Wahyuda, Aditya Muhammad Daekan; Kamil, Jubron Muflih; Al Hammaam, Hudzaif; Raihan, Muhammaf; Al Hadad, Muhammad Haqi; Absa, Rafif Yuliza; Hasbi, Noval; Al Faqih, Muhammad Fahmi (SINAR SANG SURYA, 2024)
This article discusses efforts to optimize religious science learning in the Darul Muttaqien Qur'an Education Park (TPA) Ngadirojo Village, Sooko District, Ponorogo Regency, through the Thematic Real Work Lecture (KKNT) program implemented by students of Darussalam Gontor University. The background of the discussion included the lack of community understanding of Islamic teachings in Ngadirojo Village due to the lack of teaching staff at the landfill. The method of implementing KKNT includes various activities, such as interviews related to village conditions, implementation of learning at landfill, Pondok Ramadhan activities, and competitions as learning evaluations. The results of KKNT activities show a significant improvement in the knowledge and skills of Darul Muttaqien landfill children in Islamic religious science, as well as a positive social impact on the people of Ngadirojo Village. In addition, the KKNT team also provided waqf results in the form of learning modules and learning posters to make a sustainable contribution to religious and religious education in the village